Parapneumonic empyema diagnosed by chest radiograph and computed tomography - David M. Widlus; John Paul Brady; Ning Jin (Greater Baltimore Medical Center, 2013)
Pleural effusion is commonly seen associated with pneumonia. When this progresses to empyema, directed therapy is frequently required. Chest radiographic and computed tomography findings can help distinguish empyema from a transudative pleural effusion.